2012
DOI: 10.2337/db11-0832
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Overexpression of Vascular Endothelial Growth Factor Protects Against Diet-Induced Obesity and Insulin Resistance

Abstract: During the expansion of fat mass in obesity, vascularization of adipose tissue is insufficient to maintain tissue normoxia. Local hypoxia develops and may result in altered adipokine expression, proinflammatory macrophage recruitment, and insulin resistance. We investigated whether an increase in adipose tissue angiogenesis could protect against obesity-induced hypoxia and, consequently, insulin resistance. Transgenic mice overexpressing vascular endothelial growth factor (VEGF) in brown adipose tissue (BAT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
237
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(268 citation statements)
references
References 51 publications
23
237
2
6
Order By: Relevance
“…Hypoxia-induced pro-angiogenic factors such as VEGF would then stimulate angiogenesis, thus enhancing blood and oxygen supply and reducing hypoxia in the expanded tissue. This possibility is supported by the finding that adipocytes can secrete numerous potent pro-angiogenic factors, some in response to hypoxia (11), and that VEGF-A expression can mitigate the development of metabolic dysfunction in response to a high fat diet (HFD) 2 (12,13). However, recent studies suggest that hypoxia of adipose tissue may not reach levels sufficient to elicit a pro-angiogenic response (14) and that expression of HIF-1␣ in adipocytes results in fibrosis rather than angiogenesis (15).…”
mentioning
confidence: 68%
“…Hypoxia-induced pro-angiogenic factors such as VEGF would then stimulate angiogenesis, thus enhancing blood and oxygen supply and reducing hypoxia in the expanded tissue. This possibility is supported by the finding that adipocytes can secrete numerous potent pro-angiogenic factors, some in response to hypoxia (11), and that VEGF-A expression can mitigate the development of metabolic dysfunction in response to a high fat diet (HFD) 2 (12,13). However, recent studies suggest that hypoxia of adipose tissue may not reach levels sufficient to elicit a pro-angiogenic response (14) and that expression of HIF-1␣ in adipocytes results in fibrosis rather than angiogenesis (15).…”
mentioning
confidence: 68%
“…In cultured brown adipocytes, Vegf enhanced cell survival and proliferation, whereas VEGF-neutralizing antibodies caused apoptosis 92 . Notably, overexpression of Vegf in adipose tissues of mice increases BAT mass, stimulates beiging and promotes a healthy metabolic profile 93,94 . Vegf inhibition has also been shown to reduce metabolic disease in mice, although this effect was in the context of obese WAT that was already dysfunctional 94,95 .…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%
“…It is conceivable that VEGF/VEGF-R2 blockade and associated higher circulating VEGF levels in this model result in an improvement in glucose metabolism and in insulin signaling, as previously observed with ob/ob mice (Sun et al 2012). Furthermore, it was recently shown that overexpression of VEGF in the mouse was associated with improved whole body insulin sensitivity and glucose tolerance (Elias et al 2012). It was also reported that soluble VEGF-R2 is increased in sera of subjects with metabolic syndrome and insulin resistance (Wada et al 2012).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the VEGF/VEGF-R system may play a role in insulin resistance (Elias et al 2012). In this study, we have evaluated whether VEGF-R2 blockade affects adipose tissue-related angiogenesis and fat mass or insulin signaling in mice with established nutritionally induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation